The Investigation of Multiple Intelligence Modalities of University Students Receiving Sports Education - Yildiz, Mevlüt; Öntürk, Yavuz; Efek, Engin (Asian Journal of Education and Training, 2020)
The aim of this study is to determine the dominant intelligence modality of university students who receive sports education and to examine intelligence modality in terms of various variables. The survey model was chosen for the model of the study. 251 students voluntarily participated in the study. A 6-question Personal Information Form was used by the researchers to determine the demographic characteristics of the participants, and the Multiple Intelligence Scale adapted in Turkish by Babacan and Dilci (2012) was used to determine the multiple intelligence areas. According to the findings, the intelligence modality in which the participants were the most dominant was physical intelligence, and the intelligence modality in which they were the most distant was the verbal intelligence. While multiple intelligence areas differed according to the gender, class, age and sports time of the participants, there was no significant difference in multiple intelligence areas according to department and branch variables. In addition, female participants, 3rd grade students and those who have more time to do sports are more dominant in every intelligence field. As a result, it was concluded that the most dominant intelligence field is physical intelligence and that women are more dominant in multiple intelligence domains than men. It was once again revealed that the duration of sports is an important factor in the development of multiple intelligence areas of individuals.